Negative Pressure Wound Therapy Use to Decrease Surgical Nosocomial Events in Colorectal Resections (NEPTUNE): A Randomized Controlled Trial. Issue 1 (July 2019) - Murphy, Patrick B.; Knowles, Sarah; Chadi, Sami A.; Vogt, Kelly; Brackstone, Muriel; Koughnett, Julie Ann Van; Ott, Michael C.
Abstract : Objective: Determine if negative pressure wound therapy (NPWT) reduces surgical site infection (SSI) in primarily closed incision after open and laparoscopic-converted colorectal surgery. Background: SSIs after colorectal surgery are a common cause of morbidity. The prophylactic effect of NPWT has not been established. We undertook this study to evaluate if, among patients undergoing open colorectal resection, NPWT, as compared with standard postoperative dressings, is associated with a reduction in the rate of postoperative SSI. Methods: In a randomized, controlled trial, 300 patients undergoing elective open colorectal surgery were assigned to receive prophylactic NPWT or standard gauze dressing. The primary end-point was 30-day SSI, as assessed by wound care experts blinded to treatment arm. Secondary outcomes included length of stay. Statistical analysis was performed on an intention-to-treat basis. A priori subgroup analysis was planned for patients who received a stoma at the time of initial operation. Results: The incidence of SSI at 30-days postoperatively was no different between experimental and control groups (32% vs 34% respectively, P = 0.68). Length of stay was also no different at a median of 7 days (IQR 5) for both groups. Among patients receiving a stoma, there was also no difference in SSI between the experimental and control groups (38% vs 33% respectively, P = 0.66). Conclusions: Prophylactic use of NPWT on primarily closed incisions after open colorectal surgery was not associated with a decrease in SSI rate when compared with standard gauze dressing. Trial Registration Number: Clinicaltrials.gov (NCT02007018)